Communication Assessment Tool for Ethically Sensitive Scenarios: ACT4Ethics - Daboval, Thierry; Lambrinakos-Raymond, Alicia; Schoenherr, Jordan R; Ward, Natalie; Moore, Gregory P; Ferretti, Emanuela (Université d'Ottawa | University of Ottawa, 2021)
Although well-designed instruments to assess communication during medical interviews and complex encounters exist, assessment tools that differentiate between communication, empathy, decision-making, and moral judgment are needed to assess different aspects of communication during situations defined by ethical conflict. To address this need, we developed an assessment tool that differentiates competencies associated with practice in ethically challenging situations: The Assessment Communication Tool for Ethics (ACT4Ethics) instrument. The competencies included in this assessment tool are grouped into three distinct categories: communication skills, civility and respectful behavior, clinical and ethical judgment and decision-making. [Updated from the version published in JMIR Research Protocols in 2019].
Keywords: Communication; Medical Education; Ethics; Assessment tool; Competency-based Design